1992
DOI: 10.1104/pp.99.2.589
|View full text |Cite
|
Sign up to set email alerts
|

Active Translation of the D-1 Protein of Photosystem II in Senescing Leaves

Abstract: ABSTRACTin gene expression. In particular, there is a selective depletion reflecting curtailed synthesis of Cytsfand b6 from the thylakoids of senescing leaves (3,25). This correlates with independent biochemical measurements showing that transport of electrons through the Cyt f/b6 complex is the rate-limiting step accounting for the decline in noncyclic electron transport (12,14). Indeed, the decline in noncyclic electron transport with advancing senescence is much more marked than the decline in the independ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0
1

Year Published

1996
1996
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 30 publications
1
7
0
1
Order By: Relevance
“…Probably reduced synthesis and enhanced proteolysis are both responsible for protein loss observed during senescence. In this regard, synthesis of all thylakoid proteins is known to be severely curtailed in senescing bean leaves except for the D1 protein of photosystem 2 [45]. The results presented in our study suggest that in the case of peroxidase a reduced synthesis might be predominant for the vast majority of the genes, therefore further supporting the existence of a functional specialization of peroxidases.…”
Section: Discussionsupporting
confidence: 74%
“…Probably reduced synthesis and enhanced proteolysis are both responsible for protein loss observed during senescence. In this regard, synthesis of all thylakoid proteins is known to be severely curtailed in senescing bean leaves except for the D1 protein of photosystem 2 [45]. The results presented in our study suggest that in the case of peroxidase a reduced synthesis might be predominant for the vast majority of the genes, therefore further supporting the existence of a functional specialization of peroxidases.…”
Section: Discussionsupporting
confidence: 74%
“…The higher rate of synthesis may reflect preferential translation of psbA message in response to greater depletion of the protein as seen in senescing leaves (Droillard et al 1992). This response may be an attempt of water-stressed plants to avoid complete depletion of the core.…”
Section: Discussionmentioning
confidence: 97%
“…It was proven that dark storage increases the plant petal abscission and leaf senescence, which is described by protein loss (Brady, 1988). There is some evidence that both synthesis reduction and proteolysis enhancement are the reasons for the protein reduction observed during senescence (Droillard et al, 1992). In our current study, the control and the highest NS concentration-treated plants showed a significant (P < 0.05) increase in MDA and ethylene content (Table 2).…”
Section: Discussionmentioning
confidence: 99%